The never tilting world - Chupeco, Rin (2019)
"After an ancient prophecy is betrayed, a world ruled by a long line of goddesses is split in two--one half in perpetual day, and the other in an endless night--and two young twin goddesses set out on separate and equally dangerous journeys to the Breach that divides them, hoping to save their broken world"--
Keywords: Goddesses -- Fiction; Twins -- Fiction; Sisters -- Fiction; Prophecies -- Fiction; Voyages and travels -- Fiction; Disasters -- Fiction; Fantasy; Fantasy fiction; Young adult fiction